Identification of Sampiri Birds Colonies Roosting Tree Species in Karakelang Island Talaud Islands North Sulawesi - Diah , Diah Irawati Dwi Arini (Forestry Department, University of Muhammadiyah Makassar, 2016)
The aims of this study was to identify the species and describe the morpohology of roosting tree used by sampiri colonies. The research was conducted form February to May 2014. Direct observation and recording morphology characteristic of the roosting tree were used as methodology. Data were analyzed descriptively and qualitatively and then displayed in the form of images and tables. There were six sampiri colonies using different roost trees. The roost trees were gehe (Pometia corriacea Radkl), binsar (Ficus variegata Blume), lawean (Sterculia sp.), dominated by gehe.